PEMBAHARUAN KURIKULUM FAKULTAS HUKUM BERBASIS RELIGIOSITAS SAINS - idris id (Jurnal ADIL, 2015)
ABSTRACTThe 1945 Constitution, pafiicutarty an the state administration sysfem, sfrpu/afes that the State-of lndonesia ls based on law (Rechsstaaf) and is not based on mere power (Machtstaat) instead. The former should be perceived as the one ruled by both formal judicial law and moral judicial law, since moral aspecfs are a/so ofutmost impoftance.The output of such sysfem should be policies,which take formal and moral aspecfs into accauni. And it isimpossible to achieve such ideal without religiaus approach,Therefore, the starting point for law supremacy to prevail is to wellprepare people involved in legal affairs-students majoring law-byredesigning paradigm in respective higher education, replacingmarket-based paradigm with religious paradigm, This will equip lawsfudenfs with spiritual and religious yalues so that they are able taemerge as true agents of change.Keywords : the legalparadigm of higher education, retigiosity